2014
DOI: 10.1103/physreve.89.032707
|View full text |Cite
|
Sign up to set email alerts
|

RNA topology remolds electrostatic stabilization of viruses

Abstract: Simple RNA viruses efficiently encapsulate their genome into a nano-sized protein shell: the capsid. Spontaneous coassembly of the genome and the capsid proteins is driven predominantly by electrostatic interactions between the negatively charged RNA and the positively charged inner capsid wall. Using field theoretic formulation we show that the inherently branched RNA secondary structure allows viruses to maximize the amount of encapsulated genome and make assembly more efficient, allowing viral RNAs to out-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 40 publications
(70 reference statements)
5
78
0
Order By: Relevance
“…Non-specific electrostatic interactions have emerged as the driving force for virus assembly through both the experimental as well as the theoretical studies [9,14,24,27,28]. In our two simple models we generalized the implementation of electrostatic interactions by coupling it to RNA topology.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific electrostatic interactions have emerged as the driving force for virus assembly through both the experimental as well as the theoretical studies [9,14,24,27,28]. In our two simple models we generalized the implementation of electrostatic interactions by coupling it to RNA topology.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The overcharging phenomenon has been discussed in many theoretical papers with different conclusions dependening mostly on the details of the model under consideration [26][27][28][29][30][31][32][33]. What one would hope for is that the important characteristics of the RNA genome packaging would robustly depend on some well defined characteristics of the genome, a hypothesis recently proposed in our work [24], where we showed that the secondary structure of RNA, as quantified by its branchiness, coupled to electrostatic interactions enhances the genome encapsidation capacity and could robustly explain the overcharging actually observed in virions.…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, the observation that the interiors of most RNA viruses are (negatively) overcharged (2), meaning that the negative charge brought by the nucleic acid is greater than the positive charge brought by the basic residues lining the interior of the capsid, has been examined in detail (9)(10)(11)(12). While recent coarse-grained molecular dynamics simulations (11,(13)(14)(15)(16)(17) have begun to elucidate the role of electrostatics during assembly, experimental data remain scarce due to the difficulty of resolving the inherently short-lived assembly intermediates.…”
mentioning
confidence: 99%
“…We note here that while for simplicity we employed linear chains for all the calculations in this paper, we also studied the impact of branching (following the techniques used in Ref. 32 ) on the final results. Including the secondary structures of RNA makes the chain more compact and lower the free energy values for both cylindrical and conical shells, but do not change the conclusion of the paper.…”
Section: Modelmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Since the focus of this paper is on HIV particles, we employ Edwards-de GennesLifshitz theory to calculate the free energy of a linear polymer confined in a cylindrical and conical shell. [36][37][38] In the ground-state approximation of long chains, it reads…”
Section: Modelmentioning
confidence: 99%